اهتمام علماء الحديث بالقراءات القرآنية: الإمام النَّووي أنموذجًا: The Interest of Hadith Scholar on the Variant Readings of the Quran: A Case Study of Al-Imam Al-Nawawi - El- Kubesi, Ahmed (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
This study aims to clarify the scientific significances of qira’at (the variant readings of the Quran) and their effect on hadith scholar’s understanding. This understanding was concentrated from a comprehensive reading of al-Nawawi’s (d. 676AH/1277CE) introduction to Sahih Muslim along with his methodology in directing this qira’at and be used for proof. Therefore, this study employs library-based and descriptive analytical methods in order to understand these significances and effects. The article begins with a brief encounter with al-Nawawi’s explanation of Sahih Muslim and attempts to view his methods as it may have appeared within his reference to the variant readings, his endeavor of collecting the legitimate readings, how he attributes the variant readings to the original sources and address them if possible. This article concludes that al-Nawawi, may God have mercy on him, directed most of the variant readings mentioned in his explanation, and his choice heavily relied on the tawatur (broad authentication) readings, adhere to the codex and language together with evaluation on shudhudh (irregularity) of variant readings.